2021
DOI: 10.3389/fmed.2021.651600
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA EBLN3P Regulates UHMK1 Expression by Sponging miR-323a-3p and Promotes Colorectal Cancer Progression

Abstract: Background: Growing studies have demonstrated that long non-coding RNA (lncRNA) can act as crucial roles during the progression of various tumors, including colorectal carcinoma (CRC). We aimed to determine lncRNA endogenous bornavirus-like nucleoprotein (EBLN3P) expression in CRC and examine its influence on tumor behaviors of CRC cells.Materials and Methods: Quantitative real-time polymerase chain reaction was used to determine the expression levels of EBLN3P and miR-323a-3p in CRC tissues and cell lines. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Therefore, the signaling pathways underlying the observed UHMK1-regulated progression of PDAC are quite complex and involve the regulation of UHMK1 by lncRNA H19 according to our findings. However, H19 is not the only lncRNA involved in UHMK1 regulation because Xu et al., 2021 stated that lncRNA EBLN3P regulates UHMK1 expression by sponging miR323a-3p, thereby promoting colorectal cancer progression ( 29 ). Although it is unknown whether the latter described mechanism is also involved in PDAC progression, our data were consistent with the notion that reduced expression of H19 inhibits PDAC metastasis, which involves the H19-mediated regulation of miR-194 and let-7 ( 6 , 10 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the signaling pathways underlying the observed UHMK1-regulated progression of PDAC are quite complex and involve the regulation of UHMK1 by lncRNA H19 according to our findings. However, H19 is not the only lncRNA involved in UHMK1 regulation because Xu et al., 2021 stated that lncRNA EBLN3P regulates UHMK1 expression by sponging miR323a-3p, thereby promoting colorectal cancer progression ( 29 ). Although it is unknown whether the latter described mechanism is also involved in PDAC progression, our data were consistent with the notion that reduced expression of H19 inhibits PDAC metastasis, which involves the H19-mediated regulation of miR-194 and let-7 ( 6 , 10 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…UHMK1 also contributes to purine metabolism reprogramming by regulating the NCOA3/ATF4 axis and significantly promotes gastric cancer development [ 21 ]. A recent study showed that EBLN3P promotes tumor development via targeting miR-323a-3p/UHMK1 in CRC [ 33 ]. In addition, UHMK1 expression is under the control of oxidative phosphorylation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-323a-3p is located on chromosome 14q32.31 and acts as a tumor suppressor gene in CRC [ 36 ]. Furthermore, it has been found that the upregulation of miR-323a-3p expression can induce apoptosis and inhibit the proliferation and migration of glioma cells by targeting IGF-1R [ 37 ] and damage the progression of epithelial-mesenchymal transition in bladder cancer cells by regulating the MET/SMAD3/SNAIL circuit [ 38 ] and negatively regulate LDHA expression to disrupt glycolysis in osteosarcoma cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%